Sudomotor dysfunction in people with neuromyelitis optica spectrum disorders. (12th June 2022) - Habek, Mario; Andabaka, Marko; Fanciulli, Alessandra; Brecl Jakob, Gregor; Drulović, Jelena; Leys, Fabian; Di Pauli, Franziska; Hegen, Harald; Auer, Michael; Pekmezović, Tatjana; Mesaroš, Šarlota; Jovičević, Vanja; et al.
Abstract: Background and purpose: The aim was to determine the extent of sudomotor dysfunction in people with neuromyelitis optica spectrum disorder (pwNMOSD) and to compare findings with a historical cohort of people with relapsing–remitting multiple sclerosis (pwRRMS). Methods: Forty‐eight pwNMOSD were enrolled from four clinical centers. All participants completed the Composite Autonomic Symptom Score 31 to screen for symptoms of sudomotor dysfunction. Sudomotor function was assessed using the quantitative sudomotor axon reflex test. The results were compared with a historical cohort of 35 pwRRMS matched for age, sex and disease duration. Results: Symptoms of sudomotor dysfunction, defined by a score in the Composite Autonomic Symptom Score 31 secretomotor domain >0, were present in 26 (54%) of pwNMOSD. The quantitative sudomotor axon reflex test confirmed a sudomotor dysfunction in 25 (52.1%) of pwNMOSD; in 14 of them (29.2%) sudomotor dysfunction was moderate or severe. No difference was observed between pwNMOSD and pwRRMS in any of the studied parameters. However, symptomatic sudomotor dysfunction was more frequent in pwNMOSD ( n = 8, 22.9%) compared to pwRRMS ( n = 1, 3%; p = 0.028). In a multivariable logistic regression analysis, statistically significant predictors for symptomatic sudomotor failure were age and diagnosis of neuromyelitis optica spectrum disorder. Conclusions: Sudomotor dysfunction is common in pwNMOSD and more often symptomatic compared to pwRRMS. Abstract : Symptoms of sudomotor dysfunction were present in more than half of people with neuromyelitis optics spectrum disorder (pwNMOSD). The quantitative sudomotor axon reflex test confirmed a sudomotor dysfunction in 25 (52.1%) of pwNMOSD; in 14 of them (29.2%) sudomotor dysfunction was moderate or severe. Symptomatic sudomotor dysfunction was more frequent in pwNMOSD compared to people with relapsing–remitting multiple sclerosis.